The dreamway - Papademetriou, Lisa (Harper, an imprint of HarperCollinsPublishers, 2018)
After her twin brother is attacked, Stella Clay senses there is something different about him, but a talking mouse tells her that her brother has been kidnapped and taken prisoner in the Dreamway and it is up to her to rescue him.